Chat more and contribute better: An empirical study of a knowledge-sharing community - Xiaomeng Chen; Christopher Forman; Michael E. Kummer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We analyze whether an informal second channel for communication can improve the efficiency of knowledge transfer in an electronic network of practice. We explore this question by analyzing the effect of chat rooms in the well-known Q&A forum Stack Overflow. We identify the causal effect using a difference-in-differences approach, which exploits a feed functionality that non-selectively pushed all questions from the Q&A into the relevant chat rooms. We report two main findings: First, chat rooms reduced the time until a question in the main Q&A received a satisfactory answer. Second, chat rooms disproportionately benefited new users who asked low-quality questions. Our study has clear managerial implications: A second channel for communication can complement the main channel in online communities to enhance both efficiency and inclusion.
Keywords: L17; O31; O36; 330; Knowledge sharing; Online community; User contribution